IMPLEMENTATION OF MASS COMPARISON PRACTICUM TO REDUCE MISCONCEPTION ON LAVOISIER’S LAW AT SMAN 11 SURABAYA - Fany Aulia Nur Fadhilah; Kusumawati Dwiningsih; Bambang Purwantoro (UNESA Journal of Chemical Education, 2026)
This study aimed to identify students misconceptions regarding the law of conservation of mass and to examine the effectiveness of laboratory activities in reducing these misconceptions. The study employed a quantitative descriptive using a Pre-Experimental One Group Pretest-Posttest Design involving 33 students of class X-2 at SMAN 11 Surabaya. The study was conducted in one experimental class without a control group. The research instrument used was a three-tier diagnostic test consisting of the categories understanding, misconception, not understanding, and uncertainty. Data were collected through observation, documentation, pretest and posttest. Data analysis was conducted using the Shapiro-Wilk normality test, Wilcoxon signed-rank test, and N-gain calculation with the assistance of SPSS version 32. The results showed that the percentage of students experiencing misconceptions decreased from 82% in the pretest to 3% in the posttest, while the percentage of students in the understanding category increased from 15% to 97%. The Wilcoxon Signed-Rank Test showed a significance value of <0,001, indicating that H0 was rejected and H1 was accepted. In addition, the average N-gain score was 0,9294, which falls into the high category. These findings indicate that the implementation of a mass comparison laboratory activity was effective in reducing students misconceptions and improving their understanding of the law of conservation of mass through direct empirical learning experiences and conceptual reconstruction.